(untitled) (Research, Society and Development, 2023)
This work is the result of a research completed and presented in the form of a course conclusion work in chemistry teaching. A diagnosis produced at the school unit where the research took place, in which notes from teachers and students revealed a lack of student proficiency in the concepts of acids and bases was its main justification. The objective was to qualify the assimilation schemes for the concepts of acids and bases of the students involved and, through a teaching action, verify if there was a modification of these schemes to accommodations. The main theorist used was Jean Piaget, from whom he derived the categories assimilation, accommodation and adaptation, used to analyze the data. Data collection took place in a school environment, with students, in the context of a primarily practical chemistry workshop that lasted a whole week (20 hours). The methodology used was qualitative, and the research-action method, given that the intention was to intervene by modifying reality, in this case producing learning. The classes were promoted with intense participation of the students. The results pointed to a non-adaptation of the students to the concepts of acids and bases, because after a week of effective participation in experiments, they did not demonstrate the minimum accommodation that would allow them to make scientific inferences about these concepts. In the classroom, they will most likely remember only the H+ or OH- groups, and in the laboratory they will not be able to classify an acid or a base without these groups being explained on the label in this way.